Successful rescue of a patient with cardiogenic shock following traumatic cardiac arrest using VA-ECMO after air medical transport: a case report - Haohao Wu; Pin Lan; Kechun Zhou; Lutao Xie (Frontiers in Cardiovascular Medicine)
BackgroundTraumatic cardiac arrest (TCA) poses significant challenges in resuscitation, with extremely high mortality rates, making it a critical issue in emergency and critical care medicine. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) has emerged as a crucial rescue technology for patients with cardiac arrest, providing short-term support for cardiopulmonary failure. However, the successful application and related clinical experience of VA-ECMO in TCA remain limited and require further investigation.Case presentationA male patient sustained a stab wound to the left lower limb, resulting in femoral artery and vein injuries, massive hemorrhage, and subsequent hemorrhagic shock. The patient experienced cardiac arrest upon admission to a local hospital. Following cardiopulmonary resuscitation (CPR) and emergency femoral vascular reconstruction surgery, spontaneous circulation was temporarily restored, but the patient remained hemodynamically unstable postoperatively. Initial treatment at the local hospital was ineffective. On the second morning, the patient was transferred to our hospital via air medical transport, with a transport time of 35 min. Upon arrival, the patient was promptly evaluated, and VA-ECMO support was initiated within 17 min. After 3 days of VA-ECMO support and 5 days of mechanical ventilation, the patient was successfully weaned from life support and discharged in good condition.ConclusionVA-ECMO can significantly improve the survival outcomes of patients with cardiogenic shock following traumatic cardiac arrest. The use of interhospital air medical transport effectively reduces rescue time, providing critical opportunities for the timely management of severely ill patients.